Lexicografía académica y lexicografía didáctica: ¿relaciones excluyentes o conceptos complementarios? - Hernández, Humberto (El Colegio de México, 2015)
Despite the prestige of the Royal Spanish Academy and the enormous influence it wields in the world of Hispanic lexicography, the Institution has never considered the need to change its general criteria, nor, more specifically, to adapt its dictionaries to suit the requirements of the different groups of people who use them. The Academy makes a clear-cut distinction separating what it considers to be “academic” from what it considers to be “didactic”; its policy regarding lexicography is devoid of clear objectives; and it can also be criticized for having taken insufficient advantage of the resources available to it. All this, as the present article attempts to demonstrate, doubtlessly explains why academics lexicographical studies today offer such a disjointed  and heterogeneous image.